Influence of Fe substitution into LaCoO₃ electrocatalysts on oxygen-reduction activity - Wang, Maoyu (2021)
The development of commercially friendly and stable catalysts for oxygen reduction reaction (ORR) is critical for many energy conversion systems such as fuel cells and metal-air batteries. Many Co-based perovskite oxides such as LaCoO₃ have been discovered as the stable and active ORR catalysts, which can be good candidates to replace platinum (Pt). Although researchers have tried substituting various transition metals into the Co-based perovskite catalysts to improve the ORR performance, the influence of substitution on the ORR mechanism is rarely studied. In this paper, we explore the evolution of ORR mechanism after substituting Fe into LaCoO₃, using the combination of X-ray photoelectron spectroscopy, high-resolution X-ray microscopy, X-ray diffraction, surface-sensitive soft X-ray absorption spectroscopy characterization, and electrochemical tests. We observed enhanced catalytic activities and increased electron transfer numbers during the ORR in Co-rich perovskite, which are attributed to the optimized e g filling numbers and the stronger hybridization of transition metal 3d and oxygen 2p bands. The discoveries in this paper provide deep insights into the ORR catalysis mechanism on metal oxides and new guidelines for the design of Pt-free ORR catalysts.